2015
DOI: 10.1093/aobpla/plv080
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of waterlogging in cotton and opportunities for mitigation of yield losses

Abstract: Cotton is a major world crop that is notoriously susceptible to waterlogging damage, particularly when cultivated on fine-textured soils. However, damage is also exacerbated because of inadequate acclimation of roots to low oxygen levels, and secondary effects on shoots. Despite the commercial importance of cotton, very little has been published when compared with waterlogged cereals. This review provides a comprehensive view of the constraints on cotton in low-oxygen conditions, including absence of aerenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 107 publications
(171 reference statements)
4
89
1
2
Order By: Relevance
“…For that reason, stem diameter could show a lower diameter in waterlogging plants. In general, several studies on the effects of flooding in crop plants have showed that morphological adjustments (such as plant height, stem diameter, adventitious roots, and hypertrophic lenticels) contribute to flood acclimatization (Liu et al, 2014;Najeeb et al, 2015;Phukan et al, 2016). In the present study, plant height and stem diameter did not increase, indicating that these lacks of changes suggest that S. betaceum could not achieve flood tolerance in spite of an optimum N nutritional status.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…For that reason, stem diameter could show a lower diameter in waterlogging plants. In general, several studies on the effects of flooding in crop plants have showed that morphological adjustments (such as plant height, stem diameter, adventitious roots, and hypertrophic lenticels) contribute to flood acclimatization (Liu et al, 2014;Najeeb et al, 2015;Phukan et al, 2016). In the present study, plant height and stem diameter did not increase, indicating that these lacks of changes suggest that S. betaceum could not achieve flood tolerance in spite of an optimum N nutritional status.…”
Section: Resultscontrasting
confidence: 52%
“…Also, it is important to consider that under O2 deficiency in the root zone can change the redox state of nutrients, making them unavailable (e.g. nitrogen) (Najeeb et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…These belowground effects affect the shoots, interfering with canopy development [17]. In this study,waterlogging reduced the morphological and yield parameters of cotton as well, and the longer the waterlogging duration was, the greater the reduction in these parameters.…”
Section: Discussionmentioning
confidence: 62%
“…Waterlogging-induced O 2 deficiency could be one of the most important factors responsible for yield reduction in cotton due to ethylene biosynthesis in plants tissue under waterlogged environments (Najeeb et al 2015b). Waterlogging affects cotton growth and yield, associated with the cumulative time for which the root system is exposed to low soil O 2 concentration (O 2 < 10%), soil type, and crop growth stage (Milroy et al 2009).…”
Section: Waterloggingmentioning
confidence: 99%